2001
DOI: 10.1002/1521-3765(20010504)7:9<1845::aid-chem1845>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

The Synthesis of (+)-Allopumiliotoxin 323B′

Abstract: This paper describes the synthesis of (+)-allopumiliotoxin 323B' (1) using the intramolecular [3 + 2]-cycloaddition reaction of the (Z)-N-alkenylnitrone 4. This synthesis began with (R)-tert-butyl-3-hydroxy-pent-4-enoate [(R)-13] which was obtained by enzymatic resolution with Amano PS lipase. A series of manipulations gave intermediate 17 and in situ coupling with 4-benzoyloxybutanal lead to the (Z)-N-alkenylnitrone 4 which underwent an intramolecular [3 + 2]-cycloaddition reaction to give the isoxazolidine 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…β -Hydroxy ester 10 (readily available by enzymatic resolution of the corresponding racemic aldol adduct9) served as the departure point for the valine-containing fragment and completion of the synthesis (Scheme 2). EDCI-mediated coupling with FmocValOH and subsequent Fmoc removal with diethylamine gave 4 in 62% yield for the two steps.…”
mentioning
confidence: 99%
“…β -Hydroxy ester 10 (readily available by enzymatic resolution of the corresponding racemic aldol adduct9) served as the departure point for the valine-containing fragment and completion of the synthesis (Scheme 2). EDCI-mediated coupling with FmocValOH and subsequent Fmoc removal with diethylamine gave 4 in 62% yield for the two steps.…”
mentioning
confidence: 99%
“…Indeed, Holmes and co-workers have reported that methylmagnesium bromide addition to N -Cbz-protected piperidin-3-one 8 produced exclusively the trans -methylation product 9 [44] (Scheme 3). In that case, the N -benzyloxycarbonyl group imposed A 1,3 -strain on piperidine derivatives founded the basis for the observed stereocontrol.…”
Section: Resultsmentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27][28][29][30][31] We found PS-C lipase (Pseudomonas cepacia immobilized on ceramic particles) to be as efficient as PS-Amano lipase in this operation giving the known tert-butyl (R)-3-hydroxy-4-pentenoate (+)-1 in >95% ee and 45% yield. 32 The secondary hydroxyl group was protected under standard conditions as its tert-butyldimethylsilyl ether (+)-2.…”
Section: Methodsmentioning
confidence: 99%